Peculiarities of cellular compositions of peripheral blood and immune status of humans in Antarctic conditions - Stezhka, V. A.; Moiseyenko, Ye. V.; Dmytrukha, N. M.; Bil’ko, T. O.; Bakunovsky, O. M. (Ukrainian Antarctic Journal, 2003)
Assessment of individual adaptation of 22 pretenders for long-term contract work in Antarctic in 2001-2002 and 11 winterers in early adaptation period (for 2 weeks) to new social-ecological environment in Akademik Vernadsky and after return from the station in a year was carried out.